ANALISIS PELANGGARAN ETIKA DALAM DEBAT PRESIDEN–WAKIL PRESIDEN TAHUN 2024: Pendekatan Analisis Konten - Rambe, Ahmad Sampurna; Agni, Mahisa; Sherlliana; lajuba, Sophia; Matondang, Juliana Damayanti; Siregar, Irfan Maulana (Yayasan Amanah Nur Aman, 2025)
This research analyzes ethical violations in five presidential and vice presidential debate sessions in the 2024 Election using a qualitative approach based on content analysis. The main data sources come from debate video transcripts, code of ethics documents, and media coverage. Each statement is classified according to five indicators: information quality, clarity, relevance, politeness, and public responsibility. The findings show a significant tendency for violations: the use of technical jargon without explanation, unverified data claims, veiled personal attacks, polarizing rhetoric, and simplification of complex issues. For example, in the vice presidential debate, Gibran used the term SGIE and rhetorical techniques to attack other statements, which were conveyed as “unethical” communication due to minimal context or explanation. The third presidential debate was also dominated by an ad hominem style that triggered polarization and reduced the substance of public discourse. These results support Grice's pragmatic theory and Habermas's deliberative theory on the importance of transparency, respect, and rationality in public debate. Continuous violations of broadcasting debates as a means of political education increase societal polarization and reduce public trust. Recommendations include improving debate moderation, direct verification by the media, and implementing a stricter code of ethics in each national debate session.